Sliding mode pressure controller for an electropneumatic brake: Part II—parameter identification and controller tests. (May 2018) - Luo, Zhuojun; Wu, Mengling; Zuo, Jianyong
In this article, the parameters of the sliding mode pressure controller proposed in part I of this article are identified using direct and indirect methods. A test bench, including hardware and software, is designed to test the performance of the controller. Step response tests are carried out to test controller transient and steady-state control performances. Pressure tracking tests, in which the pressure in the brake cylinder chamber is required to track sinusoidal reference signals, are carried out to test the magnitude and phase frequency characteristics of the closed-loop system. The test results suggest that the proposed controller has excellent closed-loop control performances. It can make full use of the available bandwidth of the electropneumatic brake and regulate the brake cylinder pressure to its required value quickly and precisely without obvious overshoot or undershoot in the step response tests. Steady-state error in the step response tests is no more than ±6 kPa. In the pressure tracking tests, the controller can make the brake cylinder pressure accurately track sinusoidal reference signals at low frequencies. The magnitude and phase frequency characteristics of the closed-loop system with different tube lengths and inner diameters are also given.